Pendampingan Penyusunan Standar Operational Prosedur (SOP) Pengelolaan Bank Sampah Di Kelurahan Klitren Yogyakarta - Emy - Setyaningsih; Defrensia Apriliani Kasi; Sekar Chairunnisa Purnomo; Alan Primayoga; Hendrik Saputra; Nur Annisa Syafitri; Vianney Laura Seran (LPPM IT Telkom Purwokerto, 2024)
Waste Bank is a community-based waste management system that allows the community to actively participate in managing their environment. To date, in the Klitren Sub District area, there are 16 waste banks in each RW, named Anugrah Waste Bank (BSA). In carrying out its duties and functions, each BSA has waste management policies and operational techniques that vary from one BSA to another. This causes BSA performance to be ineffective and makes it not easy for Group Facilitators to report to the Village level. Therefore, Standard Operational Procedures (SOP) are needed to regulate effective and efficient waste bank management. Community Service Activities by the ORMAWA BEM PPK Team, AKPRIND Yogyakarta Institute of Science & Technology is to provide assistance and help prepare SOPs related to excellent and effective waste bank management. The methods used are Preparation through Community Organizing and Social Mapping activities, assistance through Forum Group Discussion (FGD) activities, and Post-mentoring activities for preparing SOPs. The formation of BSA management SOPs provides clear and standardized guidance for sorting, processing, and selling waste and recording and reporting administration for BSA administrators in Klitren Village.